Evaluation of Students' Attitudes in Science Learning: Comparison Between Public and Private Junior High Schools - Maison, Maison; Kurniawan, Dwi Agus; Zain, Muhammad Sofyan (Journal of Education Research and Evaluation, 2021)
The negative attitude of students is a problem that interferes with the science learning process in public and private schools. This study aims to evaluate students' attitudes towards science subjects by comparing private and public schools. The type of research used is mix method which is descriptive in nature. The instrument of this type of quantitative research was in the form of a questionnaire, while the qualitative instrument was in the form of interview sheets for students and teachers of science subjects. The number of quantitative samples was 236 students with purposive sampling technique, while the sample of qualitative students was 8 students and 2 science teachers. The result is that students' attitudes towards science subjects in public and private junior high schools are good. The comparison results show that public junior high school students have a slightly more positive attitude than private ones